2006
DOI: 10.1016/j.ymthe.2006.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Mistargeting of Therapeutic Enzyme in Skeletal Muscle in Pompe Disease

Abstract: Enzyme replacement therapy (ERT) became a reality for patients with Pompe disease, a fatal cardiomyopathy and skeletal muscle myopathy caused by a deficiency of glycogen-degrading lysosomal enzyme acid alpha-glucosidase (GAA). The therapy, which relies on receptor-mediated endocytosis of recombinant human GAA (rhGAA), appears to be effective in cardiac muscle, but less so in skeletal muscle. We have previously shown a profound disturbance of the lysosomal degradative pathway (autophagy) in therapy-resistant mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
150
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 168 publications
(166 citation statements)
references
References 36 publications
9
150
0
1
Order By: Relevance
“…Furthermore, we have shown that autophagic accumulation in muscle fibers was associated with resistance to enzyme replacement therapy. [21][22][23] We now demonstrate that the underlying skeletal muscle pathology and the extent of autophagy in Pompe patients are similar to those in mice. Autophagy appears to play a major role in the pathogenesis of the disease, a finding that has important implications for the effectiveness of enzyme replacement therapy with the recombinant human acid a-glucosidase.…”
Section: Introductionsupporting
confidence: 52%
“…Furthermore, we have shown that autophagic accumulation in muscle fibers was associated with resistance to enzyme replacement therapy. [21][22][23] We now demonstrate that the underlying skeletal muscle pathology and the extent of autophagy in Pompe patients are similar to those in mice. Autophagy appears to play a major role in the pathogenesis of the disease, a finding that has important implications for the effectiveness of enzyme replacement therapy with the recombinant human acid a-glucosidase.…”
Section: Introductionsupporting
confidence: 52%
“…The defective autophagy in Pompe disease, which is blatantly evident in muscle fibers and to a certain extent in a cell model, may stem from reduced availability of energy source due to lysosomal glycogen sequestration. 44,45 A disturbed energy metabolism has recently been documented in Pompe patients with the adult form of the disease. 46 The autophagic defect contributes to the pathogenesis of muscle damage and alters trafficking of the replacement enzyme to the lysosome in Pompe disease.…”
Section: Discussionmentioning
confidence: 99%
“…46 The autophagic defect contributes to the pathogenesis of muscle damage and alters trafficking of the replacement enzyme to the lysosome in Pompe disease. 27,45,47 In this study we have addressed mitochondrial abnormalities and mitophagy in Pompe skeletal muscle-the major site of pathology and a challenge for therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal-associated membrane protein 2 (LAMP-2) deficiency is considered to be caused by genetic mutations and to lead to the extensive accumulation of autophagosomes in the muscles of mice and patients with Danon disease [22] . The impairment of autophagic flux by defective lysosomal function has been observed in an inherited disorder of skeletal and cardiac muscle, Pompe disease, which is caused by the deficiency of the glycogen-degrading lysosomal enzyme acid alpha-glucosidase [23] .…”
Section: Autophagic Flux Defects In Neurodegenerative Diseasesmentioning
confidence: 99%